A Quantitative Study: Assessing the Knowledge Regarding the HPV Virus and Cervical Cancer Among Romanian Young Women Aged Between 18 and 24 years - Brinzac, Monica; Coci, Ioana; Ionascu, Valeria (European Journal of Sustainable Development, 2019)
Human Papillomavirus (HPV) it is the most common cause of cervical cancer globally and Romania has the highest prevalence rate of cervical cancer in Europe. (Ene, L. (2015)). An approximation of 4443 cases of cervical cancer are diagnosticated annually in Romania. This disease is the third most prevalent cancer among women and second most prevalent between women aged 15- 44 years old. (Ferlay, J., Soerjomataram, I., & Ervik, M. (2013)). This study examines Romanian women between 18 and 24 years regarding their knowledge and attitudes on HPV, cervical cancer and HPV vaccine. The study sample consists of 200 women who answered the online questionnaire disseminated on Facebook through Facebook ads. Most respondents stated that their knowledge was average or above average. However, the answers did not reflect that the knowledge was average towards high as many did not know the symptomatology of the disease nor how the disease develops or possible outcomes. As well, the knowledge regarding the connection between HPV and cervical cancer, Pap smear is significantly low. It is essential to increase the knowledge of women regarding this topic as sexual transmitted diseases are a major problem in Romania. Keywords: Public Health, STDs, HPV, Cervical cancer